THE ROLE OF DIALOGUE LEADERSHIP IN BUILDING STRATEGIC PARTNERSHIP - Mustafa Sabah Hlehel; Dr. Nasreen Jassim Muhammad (Scholar Express Journals, 2022)
The research aims to determine the impact of dialogue leadership in building strategic partnership, as well as determining the nature of dialogue leadership and strategic partnership in the companies of the Iraqi Ministry of Housing and Construction, as well as showing the importance of these variables. In achieving its goals, the research is based on the descriptive analytical approach, by surveying the opinions of the sample under research through the questionnaire as the main tool in data collection, in addition to interviews. (55) phrase, and the statistical analysis concluded the most prominent results, including the adoption of dialogue leadership practices by the companies of the Ministry of Housing and Construction, which enabled them to enter into successful strategic partnerships, and they were able to employ them to positively influence the development of the intellectual and organizational approach to the practice of their strategic partnership applications, and the researcher came out with a group of The recommendations, including, work to consolidate organizational thought in relation to the practice of dialogue leadership approaches, with a focus on the dimensions of influence and contribution, as well as activating the dimensions of internal partnership and partnership with the competitor
Keywords: dialogical; leadership; strategic partnership